Perbankan Syariah vs Perbankan Konvensional: Apa Perbedaan Kinerja Keuangan? - Hari Gursida (Fakultas Ekonomi Universitas Negeri Jakarta, 2017)
The purpose of this study was to describe and analyze differences in financial performance between the Islamic Banking and Conventional Banking in terms of Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), Capital Adequacy Ratio (CAR), Return on Equity (ROE), Return on Assets (ROA), Cost Operations to Operating Income (BOPO). This study uses 12 Banks as sample, with sampling method using purposive sampling, and consists of 6 Islamic banks and 6 conventional banks.The analysis technique used is t-test. The results showed that there was a significant difference between financial performance between Sharia (Islamic) banking and conventional banking in terms of LDR, NPL, ROE, ROA and BOPO